The distribution of the gender pay gap in Austria: Evidence from matched employer-employee data and tax-records - Rene Boeheim; Klemens Himpele; Helmut Mahringer; Christine Zulehner (Johannes Kepler University of Linz, Department of Economics, 2011)
We examine the gender wage gap in Austria using new matched employer-employee data from 2007. We investigate the gap at the conditional wage distribution of men and women, and decompose it into the parts which are attributed to different characteristics and different returns to these characteristics. We find that women earn on average about 14% less than men for given characteristics, and that about 50% of the gender wage gap cannot be attributed to observable characteristics. The extent of different returns for women and men increase over the wage distribution where wage bargaining is predominantly on an individual basis (in contrast to low wage jobs, where collective bargaining contracts are binding).
Keywords: J13; J71; 330; gender wage differentials; quantile regressions; decomposition; matched employer-employee data; Lohndifferenzierung; Geschlecht; Schätzung; Österreich